"I Felt I Was Reaching a Point with My Health": Understanding Reasons for Engagement and Acceptability of Treatment Services for Unhealthy Alcohol Use in Primary Care. (March 2021) - O'Grady, Megan A.; Conigliaro, Joseph; Levak, Svetlana; Morley, Jeanne; Kapoor, Sandeep; Ritter, Melanie; Marini, Christina; Morgenstern, Jon
Introduction/Objectives: Despite increasing need, there are large gaps in provision of care for unhealthy alcohol use. Primary care practices have become increasingly important in providing services for unhealthy alcohol use, yet little is known about the reasons patients engage in these services and their views on acceptability of such programs. The purpose of this study was to examine primary care patients' reasons for engagement, experiences with, and acceptability of a primary care practice-based program for treating unhealthy alcohol use. Methods: This qualitative study was conducted in a primary care practice that was developing a collaborative care model for treating unhealthy alcohol use in primary care. Semi-structured interviews were conducted with 24 primary care patients. Data were analyzed using conventional qualitative content analysis. Results: Findings suggest that patients engaged for both internal (concerns about drinking and health) and external reasons (family or provider concern). Patient experiences in the program were shaped by their affective responses (enjoyable, enlightening), as well as therapeutic benefits (gaining new insights about drinking; staff/provider support). Acceptability was driven by core program elements (medication, therapy, integration) as well as positive impacts on drinking cognition and behavior and flexible, patient-centered approaches. Conclusions: Offering flexible and comprehensive programs with mutiple elements and both abstinence and moderation goals could also improve patient engagement and views on acceptability. Primary care practices will need to be thoughtful about the resources needed to implement these programs in terms of staffing, training, and program support.